The Relationship of Self-Care Activities with Blood Pressure of Diabetes Mellitus Type II Patients - Reny Sulistyowati; Yayang Savita; Ester Inung Sylvia; Wijaya Atmaja Kasuma; Nang Randu Utama; Gad Datak (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2022)
Diabetes mellitus (DM) and hypertension are diseases that often appear together. DM patients with hypertension are at risk for microvascular and macrovascular complications. Self-care activities that are carried out regularly will improve the health condition of DM patients, thereby reducing the risk of complications. This study aims to determine the relationship between self-care activities and blood pressure in type II DM patients at the BPJS Kesehatan Palangka Raya Prolanis Club. The research design uses correlation analysis with a cross-sectional approach; the research population is all members of the Prolanis Club BPJS Kesehatan Palangka Raya. The number of samples was as many as 35 people with the purposive sampling technique. The research instrument used a questionnaire, The Summary of Diabetes Self-Care Activities Measure (SDSCA); the collected data was analyzed using the chi-square test. The results showed that as many as (51.4%) of diabetic patients had good self-care activity status, totaling 18 respondents. As many as 51.4% of respondents have normal blood pressure status. The statistical results of this study obtained p value = 0.028 (p <0.05), and r = 6.240, meaning that there is a relationship between self-care activities and blood pressure in type II DM patients. It means that the higher the self-care activity in diabetic patients, the blood pressure tends to be normal. Recommendations for further research are identifying the inhibiting factors in self-care activities for type II DM patients.